EVALUASI PERLAKUAN AKUNTANSI PENDAPATAN BUNGA DAN PINJAMAN BUNGA PADA LAPORAN KEUANGAN KOPDIT (CU) NGUDI RAHAYU BERDASARKAN PERMEN KUKM NO. 13/PER.M.KUKM/IX/2015 DAN SAK ETAP - Budi Tri Rahardjo, Ak., M.Ak., CA; Rika Ikawati (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2018)
This research was the conclusion obtained from the results of this study that the transaction on Kopdit (CU) Ngudi Rahayu has been in accordance with the concept of transaction recognition based on Candy KUKM and SAK ETAP, transactions are recognized and recorded on an accrual basis, ie transactions are recognized when the transaction occurs. Kopdit (CU) Ngudi Rahayu has presented balance sheet, residual result of business report, estimated ledger report, member loan balance report, stock balance balance and daily interest balance report. However, Kopdit (CU) Ngudi Rahayu has not completed its financial reporting in accordance with the cooperative reporting regulation contained in the Minister of Cooperatives and Trade Regulation No. KUKM. No. 13 / Per / M.KUKM / IX / 2015 and SAK ETAP, and the necessary advice should be better if the financial statements have been made in accordance with applicable cooperative reporting rules.